Proceedings of the Fifth International Seminar on English Language and Teaching (ISELT 2017) 2017
DOI: 10.2991/iselt-17.2017.31
|View full text |Cite
|
Sign up to set email alerts
|

Reading Experiences on the Personal Exploration of Reading Histories of Students of FKIP Universitas Riau

Abstract: Abstract-Students'reading experiences are meaningful to be explored in order to attract their interest in reading.This study aimed to explore how the English department students of FKIP Universitas Riau experienced reading based on Exploring Personal Reading Histories. It was a case study and the data were collected through the document of the students'reading histories. The result of this study found that the English Department students of FKIP Universitas Riau experienced reading by reading through pictures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
(2 reference statements)
0
3
0
Order By: Relevance
“…A study on Exploring Personal Reading Histories in Extensive Reading course of the English Department students of FKIP University of Riau shows that students experienced reading by reading through pictures in childhood and by reading stories in the first language. In reading English texts, they experienced reading a lot of reading materials, sharing others, and reading for entertainment and knowledge (Delfi, 2017). Another context of a study shows that the reading experiences are individual contexts and processes in gaining goals in becoming competent for each level (Delfi et al, 2018).…”
Section: Exploring Reading Personal Reading Histories; a Classroom Acmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on Exploring Personal Reading Histories in Extensive Reading course of the English Department students of FKIP University of Riau shows that students experienced reading by reading through pictures in childhood and by reading stories in the first language. In reading English texts, they experienced reading a lot of reading materials, sharing others, and reading for entertainment and knowledge (Delfi, 2017). Another context of a study shows that the reading experiences are individual contexts and processes in gaining goals in becoming competent for each level (Delfi et al, 2018).…”
Section: Exploring Reading Personal Reading Histories; a Classroom Acmentioning
confidence: 99%
“…Studies show various experiences faced by learners in practicing Exploring Personal Reading Histories. Delfi (2017) found that the English Department students of FKIP University of Riau experienced reading by reading through pictures in childhood and by reading stories in the first language. In reading English texts, the learners experienced reading by understanding words, rereading the texts, reading a lot of reading materials, sharing others, and reading for entertainment and knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…However, practicing reading is not the same for all learners (Pammu, 2017). Delfi (2017) found that the experiences of Indonesian learners majoring in English were reading through pictures in childhood and reading stories in the first language, meanwhile in reading English, they experience reading by understanding words, rereading texts, reading a lot of reading materials, sharing others, and reading for entertainment and knowledge in Indonesia. Therefore, this research answered two questions: (1) What are the reading experiences of English study program learners of the Faculty of Teacher Training and Education University of Riau based on Exploring Personal Reading Histories?"…”
Section: Introductionmentioning
confidence: 99%